1995
DOI: 10.1207/s15327663jcp0401_02
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive Hedonics: Consumer Beliefs About the Dynamics of Liking

Abstract: Consumer beliefs about influences on liking are explored. Questionnaires were administered to explore the extent to which respondents’ implicit beliefs resemble any of six concepts established in experimental psychology. Results indicate respondents apply beliefs consistent with classical conditioning and Weber's law and expect adaptation to occur in a wide variety of situations. They do not show a general belief in cognitive dissonance effects. They probably do not believe in affective opponent processes (reb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 51 publications
(38 reference statements)
4
46
0
Order By: Relevance
“…The available evidence supports the more skeptical position. Studies of lay beliefs about the dynamics of taste and hedonic experience have shown these beliefs to be fragmentary and sometimes seriously inaccurate [Snell, Gibbs, and Varey 1995]. For example, the large effects of sheer familiarity in increasing liking and enjoyment are not generally known.…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence supports the more skeptical position. Studies of lay beliefs about the dynamics of taste and hedonic experience have shown these beliefs to be fragmentary and sometimes seriously inaccurate [Snell, Gibbs, and Varey 1995]. For example, the large effects of sheer familiarity in increasing liking and enjoyment are not generally known.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although people vary greatly in their intuitions about how hedonic experiences progress over time (Snell, Gibbs, and Varey 1995), they generally tend to underestimate the extent to which they adapt to experiences (Loewenstein and Frederick 1997). For instance, people underestimate their adaptation to a moderately irritating noise (Nelson and Meyvis 2008) and overestimate the duration of their affective reaction to discrete events (Wilson and Gilbert 2003).…”
Section: Disrupting Adaptation To Television Programsmentioning
confidence: 99%
“…One approach is by forecasting-the consumer first considers how she is likely to feel in response to the event ("I'll be very unhappy if the Red Sox lose today") and then considers the effects of future circumstances, such as the passage of time and how she is likely to feel in a future period ("But I'll probably feel better in a few days with my birthday coming up"). Forecasting, as an approach to predicting the hedonic impact of a future event, has been widely studied in the literature (Coughlan and Connolly 2001;Dunn, Wilson, and Gilbert 2003;Finkenauer et al 2007;Gaunt, Sindic, and Leyens 2005;Gilbert et al 1998Gilbert et al , 2004Kahneman and Snell 1992;Loewenstein and Frederick 1997;Mellers 2000;Read and Van Leeuwen 1998;Snell, Gibbs, and Varey 1995;Wilson et al 2000Wilson et al , 2005. A second approach that we propose for predicting the hedonic impact of a future event-backcasting-is one that has received much less attention.…”
Section: John Deighton Served As Editor and Baba Shiv Served As Assocmentioning
confidence: 99%
“…Two primary causes of this impact bias are focalism, where people overestimate how much they will think about the impacting event while underestimating the effect of other events on their thoughts and feelings (Wilson et al 2000), and immune neglect, where people fail to appreciate how readily they will adapt emotionally to the impacting event and so underestimate how quickly their feelings dissipate over time (Gilbert et al 1998;Snell et al 1995).…”
Section: Forecastingmentioning
confidence: 99%
See 1 more Smart Citation